Patek Philippe, or the Art to Tax Luxuries - Klaus W. Zimmermann; Tobias Thomas (Universität der Bundeswehr Hamburg, Fächergruppe Volkswirtschaftslehre, 2003)
Recent experience shows that under certain conditions it can be assumed that de-mand for luxury goods is partly abnormal. To tackle the problem whether they can and should be taxed we (a) show that a positive slope of demand is possible by distinguishing snob and network benefits, (b) demonstrate that a willingness to pay systematically lower than the equilibrium price can be explained by false trading procedures resulting (c) from the distinction between sequential and repetitive purchases. Concerning the absolute size of excess burden, a luxury tax should be levied on goods with a high elasticity of demand, but according to the relative criterion under certain (realistic) conditions low ratios may be realized by taxing goods with a high or a low elasticity. Conducting a sensitivity analysis, we conclude that in taxing luxuries there is a high risk of generating just the opposite of what was originally intended.
urn:nbn:de:gbv:705-opus-1475
Keywords: 330; Luxussteuer; Konsuminterdependenz; Steuerwirkung; Excess Burden; Optimale Besteuerung; Theorie